Generalized Class of Some Novel Estimators under Ranked Set Sampling - Rajesh Singh; Anamika Kumari (Journal of the Indian Society of Agricultural Statistics, 2025)
In this paper, mean estimators under ranked set sampling are reviewed. In this paper, we have also presented some improved novel classes of estimators for estimating the population mean using auxiliary variable under ranked set sampling. We have derived the expressions for bias and mean squared error of the proposed estimators up to the first order of approximation and the proposed classes of estimators are found to be more efficient than the other estimators in this study. In an attempt to verify the efficiencies of proposed estimators, theoretical results are supported by empirical study.